A clinicoepidemiological study of skin tags and their association with metabolic syndrome - Ankita Srivastava; Ashok Kumar Khare; Lalit Kumar Gupta; Asit Mittal; Sharad Mehta; Manisha Balai; Garima Bharti (Termedia Publishing House, 2017)
Introduction. Skin tags are known to be associated with several systemic diseases such as diabetes mellitus, obesity, dyslipidemia and cardiovascular diseases. Only a few Indian studies have investigated patients with skin tags for underlying metabolic complications. Objective . To assess the clinico-epidemiological profile of patients with skin tags and evaluate them for underlying metabolic abnormalities. Material and methods . All the patients reporting skin tag(s) at the dermatology outpatient department from October 2013 to September 2014 were included in the study. A detailed general, cutaneous and systemic examination was carried out. The data were analyzed using the χ 2 test. A p-value < 0.05 was considered significant. Results. Out of 165 enrolled patients, 112 (67.88%) completed the study protocol. Females outnumbered males, the M : F ratio being 1 : 1.11. Most patients (32; 28.57%) were in the age group of 31-40 years. The majority of the patients (77; 68.75%) reported after 1 year of noticing the lesions. The most commonly affected site was the neck (99; 88.39%) followed by the axilla (53; 47.32%). Acanthosis nigricans was the most common skin disease associated with skin tags (37; 33.03%). The diagnostic criteria for metabolic syndrome were fulfilled by 47 (41.96%) patients. The majority of the patients (70; 62.5%) were either overweight or obese. Abnormal glucose tolerance and hypertension were found in 41 (36.6%) and 37 (33.03%) of the patients respectively. Above optimal LDL cholesterol was the most common lipid abnormality, detected in 64 (56.25%) of the cases. Patients with 11 or more skin tags lesions and those with involvement of the thigh, axilla or neck were more likely to have metabolic syndrome. Conclusions. Patients with skin tags should be screened for concomitant diseases such as diabetes, hypertension, dyslipidemia and cardiovascular disease. Early detection of these complications followed by appropriate lifestyle changes and/or drug therapy would be beneficial in terms of reducing the considerable morbidity and mortality.